Manhaj Salafi and its Controversial Da'wah in Youtube Vlogs - Iskandar Iskandar (International Journal of Nusantara Islam, 2021)
This study aims to understand what is meant by Manhaj Salafi and explain why his da'wah behavior is controversial in the current youtube media. The author considers this research important in the midst of the government's efforts to build a safe, comfortable, and peaceful atmosphere among fellow believers. However, the divisions and disputes among the nation's children, will certainly bring bad impacts. That is why the Indonesian Ministry of Religion is currently actively campaigning for religious moderation everywhere in order to reduce the extreme attitudes of the people in religion. With a qualitative approach, the author tries to explore and analyze the data that the author gets from various youtube vlogs. The results of the study indicate that the controversial themes of da'wah are generally issues of khilafiyah which are considered as problems of ushul by the bearers of the Manhaj Salafi. However, the unique thing is that these controversial themes appear more because of the prompting of questions from the audience who follow the lectures of the Manhaj Salafi figures. The lack of wisdom of the Manhaj Salafi da'i in da'wah as well as their mistakes in understanding the nature of da'wah have made this understanding more and more resistant in society. Not only that, even among the supporters of the Manhaj Salafis, there were contradictory attitudes towards each other. An attitude of self-restraint and mutual respect for the opinions of others needs to be built in our society. Don't let us be provoked by media like YouTube which is sometimes used by irresponsible people. The supporters of Manhaj Salafi also need to learn from their predecessors such as the Muhammadiyah organization, then make modifications and adaptations in conveying their da'wah so that their understanding can be well received by the Indonesian people. Basically the presence of this understanding brings many benefits, as well as the invitation (da'wah) of Manhaj Salafi to return to the Qur'an and al-Hadith is good and right, as long as it is carried out with an approach that is in accordance with the culture of our nation. then make modifications and adaptations in conveying their da'wah so that their understanding can be well received by the Indonesian people. Basically the presence of this understanding brings many benefits, as well as the invitation (da'wah) of Manhaj Salafi to return to the Qur'an and al-Hadith is good and right, as long as it is carried out with an approach that is in accordance with the culture of our nation. then make modifications and adaptations in conveying their da'wah so that their understanding can be well received by the Indonesian people. Basically the presence of this understanding brings many benefits, as well as the invitation (da'wah) of Manhaj Salafi to return to the Qur'an and al-Hadith is good and right, as long as it is carried out with an approach that is in accordance with the culture of our nation.